2012
DOI: 10.1177/1073858411434209
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Spatial Processing in the Human Cortex

Abstract: The auditory system codes spatial locations in a way that deviates from the spatial representations found in other modalities. This difference is especially striking in the cortex, where neurons form topographical maps of visual and tactile space but where auditory space is represented through a population rate code. In this hemifield code, sound source location is represented in the activity of two widely tuned opponent populations, one tuned to the right and the other to the left side of auditory space. Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 65 publications
2
27
0
Order By: Relevance
“…It is also consistent with human fMRI data, which has shown that primary auditory cortex is highly sensitive to both ear of stimulation (Woods et al 2010;Stecker et al 2015;Gutschalk and Steinmann 2015) and interaural level differences (ILDs) Stecker et al 2015), but not ITD (von Kriegstein et al 2008;McLaughlin et al 2015). Although ITD sensitivity has been found in human auditory cortex, it is generally located in more posterolateral areas (von Kriegstein et al 2008;McLaughlin et al 2015) and in long-as opposed to middle-latency components of the AER (McEvoy et al 1993;Salminen et al 2009;Salminen et al 2010;Magezi and Krumbholz 2010;Gutschalk et al 2012) (for reviews, see Salminen et al 2012;Gutschalk 2014). In any case, the population-level representation of ITD at the level of the midbrain might be fundamentally different from that found in primary AC (Thompson et al 2006;von Kriegstein et al 2008;Belliveau et al 2014;Vonderschen and Wagner 2014;Yao et al 2015), though this is in need of further clarification.…”
Section: Spatial Representation In the Auditory Pathwaysupporting
confidence: 68%
“…It is also consistent with human fMRI data, which has shown that primary auditory cortex is highly sensitive to both ear of stimulation (Woods et al 2010;Stecker et al 2015;Gutschalk and Steinmann 2015) and interaural level differences (ILDs) Stecker et al 2015), but not ITD (von Kriegstein et al 2008;McLaughlin et al 2015). Although ITD sensitivity has been found in human auditory cortex, it is generally located in more posterolateral areas (von Kriegstein et al 2008;McLaughlin et al 2015) and in long-as opposed to middle-latency components of the AER (McEvoy et al 1993;Salminen et al 2009;Salminen et al 2010;Magezi and Krumbholz 2010;Gutschalk et al 2012) (for reviews, see Salminen et al 2012;Gutschalk 2014). In any case, the population-level representation of ITD at the level of the midbrain might be fundamentally different from that found in primary AC (Thompson et al 2006;von Kriegstein et al 2008;Belliveau et al 2014;Vonderschen and Wagner 2014;Yao et al 2015), though this is in need of further clarification.…”
Section: Spatial Representation In the Auditory Pathwaysupporting
confidence: 68%
“…These experiments provided evidence for the 'opponent-channel coding' hypothesis, the basis of which were in vivo electrophysiological experiments on laboratory animals (Phillips and Irvine 1981;McAlpine and Grothe 2003;Werner-Reiss and Groh 2008). Further described under the name of 'hemifield model' the concept was also proposed for the representation of sound direction in humans (Stecker and Middlebrooks 2003;Magezi and Krumbholz 2010;Salminen et al 2009Salminen et al , 2010Salminen et al , 2012Briley et al 2013;review Phillips 2008). The model proposes two neural populations in each cortical hemisphere showing graded sensitivity to acoustic stimulation in the contralateral hemifield.…”
Section: Young Adult Listenersmentioning
confidence: 93%
“…One particular feature of the model is that central positions can be represented with high spatial resolution, while lateral positions are less accurately represented. Neural adaptation paradigms probing the neural change response at the level of a u d i t o r y c o r t e x i s o n e o f t w o f r e q u e n t l y u s e d magnetoencephalographic (MEG)/EEG-paradigms to study the underpinning neural encoding of auditory space (Salminen et al 2012). In this paradigm, an adaptor sound is presented from a standard position immediately followed by a probe sound from a different spatial position and the change response-in the N1-P2 time window corresponding to the probe sound-is quantified.…”
Section: Young Adult Listenersmentioning
confidence: 99%
“…In the auditory cortex, neural tuning to spatial location is a ubiquitous property: in some cortical fields, spatially selective neurons constitute >50% of all neurons (Tian et al, 2001;Woods et al, 2006). Auditory cortical neurons are widely and laterally tuned with their receptive fields spanning one hemifield of the auditory space (Woods et al, 2006;Werner-Reiss and Groh, 2008;Salminen et al, 2009;Salminen et al, 2012). Two concurrently presented sounds, one from the left and the other from the right side of the midline, would then activate separate neural populations, and thereby their segregation should be possible based on the spatial separation.…”
Section: Introductionmentioning
confidence: 99%